2017
DOI: 10.1177/0033294117730845
|View full text |Cite
|
Sign up to set email alerts
|

Self-Consciousness or Misattribution Effect in the Induced Hypocrisy Paradigm? Mirror, Mirror on the Wall…

Abstract: In a forced compliance situation, Scheier and Carver have shown that making high private self-consciousness salient through exposure to a mirror inhibits the arousal of dissonance and the subsequent attitude change. Based on these results, the aim of our study is to examine an alternate theoretical interpretation of the absence of attitude change. From our point of view, the mirror could have the status of a misattribution cue, thus maintaining the arousal. To test this hypothesis within the induced hypocrisy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
4
0
1
Order By: Relevance
“…To test this hypothesis, we used the dissonance thermometer (Elliot and Devine, 1994), a measure of self-reported affects characterizing the cognitive dissonance. Many studies on cognitive dissonance have used it, both with the induced compliance paradigm (Devine, Tauer, Barron, Elliot, and Vance, 1999;Gosling et al, 2006) and the induced hypocrisy paradigm (Fointiat et al, 2013;Pelt and Fointiat, 2017;Priolo et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To test this hypothesis, we used the dissonance thermometer (Elliot and Devine, 1994), a measure of self-reported affects characterizing the cognitive dissonance. Many studies on cognitive dissonance have used it, both with the induced compliance paradigm (Devine, Tauer, Barron, Elliot, and Vance, 1999;Gosling et al, 2006) and the induced hypocrisy paradigm (Fointiat et al, 2013;Pelt and Fointiat, 2017;Priolo et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the Negself measure seems to be sensitive to the manipulation of expressive dissonance, whatever the positive or negative valence of the inducing emotion. The dissonance thermometer is usually used in the classic paradigms of cognitive dissonance: induced compliance (Elliot and Devine, 1994;Gosling et al, 2006) and induced hypocrisy (Fointiat et al, 2013;Pelt andFointiat, 2017, Priolo et al, 2016). In the majority of studies, it is the dimension of psychological discomfort which reflects the arousal and the reduction of dissonance.…”
Section: Discussionmentioning
confidence: 99%
“…Par exemple, Zanna et Cooper (1974) vont se concentrer sur le ressenti de tension tandis que Elliot et Devine (1994) vont écarter cet item de leur mesure de dissonance. Aussi, en utilisant le même outil de mesure, les auteurs s'appuient sur des items différents pour identifier l'état de dissonance cognitive lui attribuant de fait une nature différente (e.g., Holland, Meertens, & van Vugt, 2002 ;Matz & Wood, 2005 ;Pelt & Fointiat, 2018 ;Priolo et al, 2016). Les récents modèles intégratifs continuent de considérer l'existence d'un ressenti commun mais soulignent qu'il est encore mal identifié et le décrivent d'ailleurs différemment (Jonas et al, 2014 ;.…”
Section: Renouveau Théorique Anciennes Questionsunclassified
“…Aside from the misattribution paradigm, the most popular method to study the CDS is the use of self-report scales. Studies have repeatedly shown that a negative affect was induced by a variety of cognitive dissonance paradigms, such as the classic counterattitudinal task paradigm (Cancino-Montecinos, Björklund, & Lindholm, 2018;Elliot & Devine, 1994;Harmon-Jones, 2000a;Galinsky, Stone, & Cooper, 2000;Shaffer, 1975), being reminded of self-transgressions concerning advocated behaviours (Pelt & Fointiat, 2018;Priolo et al, 2016;Yousaf & Gobet, 2013), being exposed to information inconsistent with beliefs (Russell & Jones, 1980;Vaidis & Gosling, 2011), being in disagreement with others (Matz & Wood, 2005), and seeing someone performing a counterattitudinal behaviour (i.e., vicarious dissonance; Norton, Monin, Cooper, & Hogg, 2003;Monin, Norton, Cooper, & Hogg, 2004). Most scholars using self-report scales consider that the CDS is not felt as a general negative affect but is rather experienced as a specific psychological discomfort (Elliot & Devine, 1994).…”
Section: Aversiveness Of Cognitive Dissonancementioning
confidence: 99%
“…Perhaps due to these psychometric issues, the Dissonance Thermometer is also not used in a standardized way. The discomfort index is often assessed separately from the rest of the scale (Harmon-Jones, 2000b;Galinski, et al, 2000;Monin et al, 2004;Norton et al, 2003;Vaidis & Gosling, 2011), or measured with different instructions and methods of scoring (Harmon-Jones, 2000b;Monin et al, 2004;Norton et al, 2003;Vaidis & Gosling, 2011), and some researchers alter the index by using only some of the original items (Holland, Meertens & Van Vugt, 2002) or by combining it with other items (Jordens & Van Overwalle, 2005;Matz & Wood, 2005;Pelt & Fointiat, 2018;Priolo et al, 2016). This lack of standardization impairs the comparability of the results and limits their interpretation.…”
Section: Limits On the Evidences For Cognitive Dissonance Aversivenessmentioning
confidence: 99%